2017
DOI: 10.1074/jbc.m117.792416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and modulation of microvesicle uptake in a model of alveolar cell communication

Abstract: Extracellular vesicles, including exosomes and shed microvesicles (MVs), can be internalized by recipient cells to modulate function. Although the mechanism by which extracellular vesicles are internalized is incompletely characterized, it is generally considered to involve endocytosis and an initial surface-binding event. Furthermore, modulation of uptake by microenvironmental factors is largely unstudied. Here, we used flow cytometry, confocal microscopy, and pharmacologic and molecular targeting to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 78 publications
8
64
1
Order By: Relevance
“…Importantly, CS-exposed mice and human smokers exhibited decreased SOCS concentrations in BALF compared to nonsmoking controls, suggesting a loss of EV-dependent antiinflammatory state in smokers (Bourdonnay et al 2015). In addition, the anti-inflammatory effect of alveolar macrophage-derived EV depends upon their internalization by target cells, which is inhibited by the presence of CS extract (CSE) (Schneider et al 2017). …”
Section: Interference With Anti-inflammatory Signalingmentioning
confidence: 99%
“…Importantly, CS-exposed mice and human smokers exhibited decreased SOCS concentrations in BALF compared to nonsmoking controls, suggesting a loss of EV-dependent antiinflammatory state in smokers (Bourdonnay et al 2015). In addition, the anti-inflammatory effect of alveolar macrophage-derived EV depends upon their internalization by target cells, which is inhibited by the presence of CS extract (CSE) (Schneider et al 2017). …”
Section: Interference With Anti-inflammatory Signalingmentioning
confidence: 99%
“…In initial studies with MHS cells, EVs were pelleted from MHS CM by 17 000×g ultracentrifugation for 30 minutes, with quantification of EV numbers performed as described previously. 16 During the course of our studies, we observed that the yield of EVs by this isolation method was limited due to their rupture owing to the high shear forces from ultracentrifugation. This prompted us to instead employ the gentler method of centrifugal filtration of AM CM through a 100 kDa exclusion filter (MilliporeSigma) 32 and this technique was employed for EV isolation from the J2immortalized AM cell line.…”
Section: Isolation Of Evsmentioning
confidence: 93%
“…A continuous SV40‐transformed line of primary AMs originally obtained from lavage fluid of normal mice (MHS, CRL‐2019), which we have utilized previously as a source of EVs, and a transformed human bronchial EC line (BEAS‐2B) were purchased from American Type Culture Collection. Normal primary mouse AMs were obtained by lung lavage of a male C57BL/6 wild type mouse (The Jackson Laboratory) and subsequently immortalized by infecting with the J2 retrovirus carrying v‐raf and v‐myc oncogenes as previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low pH has also been shown to promote exosome release and uptake, indicating that this may be a conserved EV characteristic. Recent studies have indicated an importance for actin polymerization and dynamin, a key protein involved in membrane budding and fission, in macropinocytic‐like MV uptake by alveolar epithelial cells . An important regulator in EV internalization is heparan sulfate proteoglycans (HSPGs), and treating EVs with heparin reduces their uptake .…”
Section: Uptake Of Evs Into Cellsmentioning
confidence: 99%